Application of the Six Sigma Method in Railway Level Crossing Construction using Concrete Level Crossing in Gedebage-Haurpugur, West Java - Silvano, Verian Gustam; Pontan, Darmawan; Zaki, M.; Kurniyaningrum, Endah (Universitas Ibn Khaldun Bogor, 2025)
The public interest in trains makes train traffic increasingly dense, resulting in congestion at railroad and highway intersections. Intersections between railways and highways are divided into level and non-level crossings. The potential impact or risk of the existence of a level crossing can cause several problems, one of which is the wheels of vehicles (motorbikes) which often slip when crossing the tracks. To reduce the potential risk of the existence of level crossings in the form of vehicle tires slipping between the rail gaps, PT. In 2022, KAI develop solutions to the problems that occur, one of the methods is by adding a concrete product in the form of Concrete Level Crossing, which is a prestressed concrete plate made with a knock down system so that it can be easily dismantled and assembled in the field without having to disrupt train travel schedules. This research was conducted to determine the most important factors in improving the quality of CLC plate construction at railway level crossings, to determine the application of the Six Sigma method to CLC plates at railway level crossings, and to determine the effect of applying the Six Sigma method to plates. CLC for railway crossings. The independent variable (X) in this research is the Six Sigma method, while the dependent variable (Y) in this research is the implementation of railroad crossing construction using Six Sigma-based Concrete Level Crossing (CLC). The questionnaire survey was carried out via an online survey. The number of respondents who provided assessments on this research questionnaire was 33 respondents from 5 related companies. The respondents taken in this research consisted of 4 experts with the expert criteria being personal experience in the field of planning and operational implementation in Concrete Level Crossing (CLC) installation work. The most important variable in improving the quality of CLC installations is the Quality Control variable. Only the Quality Control variable has an influence on the implementation of Six Sigma in CLC installations. The results of the DPMO calculation show a defect value of 31,250 per million or the equivalent of 3.59 sigma, where the quality still needs to be improved to reach a value of 6 sigma.